(untitled) (Modern education and development, 2025)
Ischemic heart disease (IHD), primarily resulting from coronary artery disease (CAD), remains a leading cause of morbidity and mortality worldwide. This article provides an in-depth analysis of the classification of IHD, including stable and unstable angina, and myocardial infarction (MI). It also discusses contemporary treatment strategies encompassing lifestyle modifications, pharmacological interventions, and revascularization procedures.